Les théories de la magie dans les traditions anthropologiques anglaise et française - Frédéric Keck (Methodos, 2004)
This article contrasts French and English traditions of anthropology in their way of handling the problem of magic, particularly as regards the two problems raised by the phenomenon of magic : what kind of rationality gives magic its efficacy although it makes no predictions ? What made possible the shift from a magical rationality to a scientific and critical rationality ? After a brief survey of the relationships between magic, science and religion as they are conceived by Tylor and Frazer, this article opposes the idea of a plasticity of magical utterances in relation to the pragmatic contexts in which they are inscribed, in the works of Malinowski and Evans-Pritchard, and the idea of a structure of magical thought that would be embodied in the acts of an individual magician, in the works of Mauss and Lévi-Strauss. The conclusion focuses on the way these two traditions have addressed the problem of the logic of practice, and the consequences that such a difference in the position of the problem of magic has for today.